2022
DOI: 10.1088/1757-899x/1251/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Overview on plasma electrolytic oxidation of magnesium alloys for medical and engineering applications

Abstract: The scope of this review article is to offer a general view of the recent advances in the plasma electrolytic oxidation of Mg and Mg alloys with emphasis of the Plasma Electrolytic Oxidation (PEO) processing parameters used to obtain key surface properties for medical and engineering applications. The paper presents the different dependencies of the PEO process, first of all depending on the composition of the substrate, the electrolyte used, the applied electrical regime, as well as the way of their interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Based on all of the studies related to this subject, it has been de- It has been observed that particle size plays a significant role in the uptake process. Nanoparticles penetrate deeper into coatings than microparticles, based on the results of other studies [97]. Large particles, on the other hand, cannot penetrate through pores on the surface of the layer.…”
Section: Incorporation Of Particles Into the Electrolytes And Mechani...mentioning
confidence: 87%
“…Based on all of the studies related to this subject, it has been de- It has been observed that particle size plays a significant role in the uptake process. Nanoparticles penetrate deeper into coatings than microparticles, based on the results of other studies [97]. Large particles, on the other hand, cannot penetrate through pores on the surface of the layer.…”
Section: Incorporation Of Particles Into the Electrolytes And Mechani...mentioning
confidence: 87%
“…Lately, PEO has become increasingly popular as a method for producing multifunctional coatings and improving the surface characteristics of magnesium and its alloys [10][11][12][13][14][15][16][17][18]. Some studies have shown that oxide coatings formed on magnesium alloys can be used in photocatalytic applications [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%